Research on NFC End-to-End Compatibility Test - Yiwei Gao; Yu Sun (Dianxin kexue)
NFC has a long industry chain with many manufacturers involved in,which brings a significant challenge to the compatibility.Four testing methods were presented to improve the compatibility of NFC terminals and POS terminals.These testing methods include more rigorous conformance testing method,instrument compatibility testing method,R/W compatibility testing method and POS compatibility testing method.Industry participants can use one or more of these four methods to improve NFC end-to-end compatibility based on their own needs,which can help optimize the NFC mobile pay environment.